Diagnostic efficacy of serological and epigenetic methods of screening diagnostics of colorectal cancer - O. I. Kit; D. V. Burtsev; A. Yu. Maksimov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Development of adequate screening and diagnostic algorithms on colorectal cancer detection.Material and methods. The main group included 204 patients with colorectal cancer (CRC),that has been revealed at screening of 1669 patients by immunochemical fecal occult blood test (FOBT). Control group included 213 CRC patients who have addressed oncologic institutions for intestinal or general complaints independently. Screening program included: immunochromatographic FOBT, blood test for tumor markers — carcinoembryonic antigen (CEA), oncoantigens СА 19-9, СА 242), methylated DNA of septin 9 gene.Results. Diagnostic efficacy of CRC screening diagnostics by testing of blood levels of CEA, СА 242 and СА 19-9 was 40,4, 50,8 and 51,7% respectively. Epigenetic tests for DNA methylate of SEPT9 gene in blood as screening procedure was characterized by high diagnostic efficacy — 86,5%. At the initial stage of screening diagnostics optimum combination of methods is immunochemical FOBT at 100 ng/ml threshold and assessment of DNA methylate of gene SEPT9 in blood. Diagnostic efficacy of the 1-st stage of screening diagnostics was 90%.Conclusions. The initial stage of screening diagnostics CRC including immunochemical FOBT tests at threshold of 100 ng/ml, assessment of DNA methylate of SEPT9 gene in blood, provide optimum ratio of sensitivity and specificity and cost efficacy.